(untitled) (مجلة البحوث الأكاديمية, 2018)
In this paper, we shall describe two nice characterizations of weak amenability of commutative Banach algebras. We shall prove the equivalence between Groenbaek’s characterization, and Johnson’s characterization for these algebras.